MORFOLOGI PERMUKIMAN MULTIETNIK DI KAMPUNG PURWODINATAN SEMARANG: INTEGRASI BUDAYA DALAM RUANG ARSITEKTUR - Susanti, Anityas Dian; Nuzuluddin, Taufiq Rizza; Wahyono, Sharfina Bella Pahleva (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
Purwodinatan Village in Semarang is one of the urban residential areas that exhibits a strong multiethnic character, with Koja, Chinese, and Javanese communities having coexisted for over a century. This study aims to examine the settlement morphology of the village and explore how the cultural values of each ethnic group are integrated into spatial forms and architectural expressions. A qualitative-descriptive approach is employed, using field observations, visual documentation, and spatial mapping to analyze street patterns, plot configurations, residential space organization, and building typologies. The findings indicate that the morphological structure of Kampung Purwodinatan has developed organically, reflecting a gradual process of cultural adaptation. The narrow streets and branching alleys illustrate a community-based social system, while the houses and architectural elements display acculturation between Middle Eastern, Chinese, and traditional Javanese styles. Cultural integration is evident not only in the physical form of the buildings but also in the use of communal spaces such as mosques, temples, and local food stalls, which serve as social meeting points that reinforce intercommunity cohesion. This study highlights the importance of understanding multicultural dynamics in the planning of historic urban areas and its relevance in preserving local identity through an inclusive architectural approach.